If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11x + -7)(2x + 5) = 0 Reorder the terms: (-7 + 11x)(2x + 5) = 0 Reorder the terms: (-7 + 11x)(5 + 2x) = 0 Multiply (-7 + 11x) * (5 + 2x) (-7(5 + 2x) + 11x * (5 + 2x)) = 0 ((5 * -7 + 2x * -7) + 11x * (5 + 2x)) = 0 ((-35 + -14x) + 11x * (5 + 2x)) = 0 (-35 + -14x + (5 * 11x + 2x * 11x)) = 0 (-35 + -14x + (55x + 22x2)) = 0 Combine like terms: -14x + 55x = 41x (-35 + 41x + 22x2) = 0 Solving -35 + 41x + 22x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -2x)(7 + -11x) = 0Subproblem 1
Set the factor '(-5 + -2x)' equal to zero and attempt to solve: Simplifying -5 + -2x = 0 Solving -5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2x = 0 + 5 -2x = 0 + 5 Combine like terms: 0 + 5 = 5 -2x = 5 Divide each side by '-2'. x = -2.5 Simplifying x = -2.5Subproblem 2
Set the factor '(7 + -11x)' equal to zero and attempt to solve: Simplifying 7 + -11x = 0 Solving 7 + -11x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -11x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -11x = 0 + -7 -11x = 0 + -7 Combine like terms: 0 + -7 = -7 -11x = -7 Divide each side by '-11'. x = 0.6363636364 Simplifying x = 0.6363636364Solution
x = {-2.5, 0.6363636364}
| 20+8h=60 | | 10x+8=180 | | (3x/(x^2-4))-1/x^2 | | 2x+2(x-4)=3x | | 25a^2-15=2a | | 9r+4=29r+9 | | 14+2r=20 | | h=12+15t+-16t^2 | | 7x-7-4x=4x-4 | | (a^2+b^2)(a+b)=0 | | x+(4x-5)=125 | | (8x+6)(-4x-6)=0 | | 30/7.5 | | h=12+15t+16t^2 | | 14b=10 | | 4x-1-3=x-11 | | 3+p=3.1 | | 2(3a+b)=h | | 9x=14+17x | | 55x+20(72x+36y)=200 | | X-2/5=-1/6 | | C=4c-8 | | -2x-9=7x+9 | | (m^3+3)(5m+n)=0 | | -8/3a=24 | | 2x^2+8x-64=1080 | | 3x^2+x^2=200 | | 3x^2(x^2)=200 | | 4(2a-3)-2(a-4)=3(a-3)-1 | | 3+4+x=1+6 | | 6(y-5)=z(10+3y) | | 5x+11y+1z=57.73 |